The ATXN2-SH2B3 locus is associated with peripheral arterial disease: an electronic medical record-based genome-wide association study - Kullo, Iftikhar J.; Shameer, Khader; Jouni, Hayan; Lesnick, Timothy G.; Pathak, Jyotishman; Chute, Christopher G.; de Andrade, Mariza (Frontiers in Genetics, 2014)
Objectives: In contrast to coronary heart disease, genetic variants that influence susceptibility to peripheral arterial disease (PAD) remain unknown. Background: We performed a two-stage genomic association study leveraging an electronic medical record linked-biorepository to identify genetic variants that mediate susceptibility to PAD. Methods: PAD was defined as a resting/post-exercise ankle-brachial index (ABI) ≤0.9 or ≥1.4 and/or history of lower extremity revascularization. Controls were patients without history of PAD. In Stage I we performed a genome-wide association analysis adjusting for age and sex, of 561,490 SNPs in 1641 PAD cases (66±11 y, 64% men) and 1604 control subjects (61±7 y, 60% men) of European ancestry. In Stage II we genotyped the top 48 SNPs that were associated with PAD in Stage I, in a replication cohort of 740 PAD cases (70±11 y, 63% men) and 1051 controls (70±12 y, 61% men). Results: The SNP rs653178 in the ATXN2-SH2B3 locus was significantly associated with PAD in the discovery cohort (OR: 1.23; P=5.59x10-5), in the replication cohort (OR=1.22; 8.9x10-4) and in the combined cohort (OR=1.22; P-value: P=6.46x10-7). In the combined cohort this SNP remained associated with PAD after additional adjustment for cardiovascular risk factors including smoking (OR: 1.22; P=2.15x10-6) and after excluding patients with ABI >1.4 (OR: 1.237; P=3.98x10-7). The SNP is in near-complete linkage disequilibrium (r2=0.99) with a missense SNP (rs3184504) in SH2B3, a gene encoding an adapter protein that plays a key role in immune and inflammatory response pathways and vascular homeostasis. The SNP has pleiotropic effects and has been previously associated with multiple phenotypes including myocardial infarction. Conclusions: Our findings suggest that the ATXN2-SH2B3 locus influences susceptibility to PAD.